Conformational stability of fibrillar amyloid-beta oligomers via protofilament pair formation - a systematic computational study - Kahler, Anna; Sticht, Heinrich; Horn, Anselm (PLoS ONE, 2013)
Amyloid-[Formula: see text] (A[Formula: see text]) oligomers play a crucial role in Alzheimer's disease due to their neurotoxic aggregation properties. Fibrillar A[Formula: see text] oligomerization can lead to protofilaments and protofilament pairs via oligomer elongation and oligomer association, respectively. Small fibrillar oligomers adopt the protofilament topology, whereas fibrils contain at least protofilament pairs. To date, the underlying growth mechanism from oligomers to the mature fibril still remains to be elucidated. Here, we performed all-atom molecular dynamics simulations in explicit solvent on single layer-like protofilaments and fibril-like protofilament pairs of different size ranging from the tetramer to the 48-mer. We found that the initial U-shaped topology per monomer is maintained over time in all oligomers. The observed deviations of protofilaments from the starting structure increase significantly with size due to the twisting of the in-register parallel [Formula: see text]-sheets. This twist causes long protofilaments to be unstable and leads to a breakage. Protofilament pairs, which are stabilized by a hydrophobic interface, exhibit more fibril-like properties such as the overall structure and the twist angle. Thus, they can act as stable conformational templates for further fibril growth. Key properties like the twist angle, shape complementarity, and energetics show a size-dependent behavior so that small oligomers favor the protofilament topology, whereas large oligomers favor the protofilament pair topology. The region for this conformational transition is at the size of approximately twelve A[Formula: see text] monomers. From that, we propose the following growth mechanism from A[Formula: see text] oligomers to fibrils: (1) elongation of short protofilaments; (2) breakage of large protofilaments; (3) formation of short protofilament pairs; and (4) elongation of protofilament pairs.
EVALuna2:26277

The effect of fulvic acid on pre- and postaggregation state of A?17-42: molecular dynamics simulation studies, S. Verma, A. Singh and A. Mishra, Biochim Biophys Acta 1834 (2013) 24-33 - Horn, Anselm; Kahler, Anna (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2013)
EVALuna2:26286